Immunology of EBV-Related Lymphoproliferative Disease in HIV-Positive Individuals - Shindiapina, Polina; Ahmed, Elshafa H.; Mozhenkova, Anna; Abebe, Tamrat; Baiocchi, Robert A. (Frontiers in Oncology, 2020)
Epstein-Bar virus (EBV) is associated with increased risk of lymphoproliferative disease (LPD), including AIDS-defining lymphomas such as Burkitt’s lymphoma and other non-Hodgkin lymphomas, as well as HIV-related Hodgkin lymphoma (HL). The prevalence of EBV in HL and non-Hodgkin lymphomas is elevated in HIV-positive individuals compared with the general population. Rates of incidence of AIDS-defining cancers in HIV-infected individuals have been declining since initiation of combination anti-retroviral therapy (cART) use in 1996. However, HIV-infected persons remain at an increased risk of cancers related to infections with oncogenic viruses. Proposed pathogenic mechanisms of HIV-related cancers include decreased immune surveillance, decreased ability to suppress infection-related oncogenic processes and a state of chronic inflammation marked by alteration of the cytokine profile and expanded numbers of cytotoxic T lymphocytes, with down-regulated co-stimulatory molecules and increased expression of markers of senescence in the setting of treated HIV infection. In this review we discuss the cooperation of EBV-infected B cell- and environment-associated factors that may contribute to EBV-related lymphomagenesis in HIV-infected individuals. Environment-derived lymphomagenic factors include impaired host adaptive and innate immune surveillance, cytokine dysregulation and a pro-inflammatory state observed in the setting of chronic, cART-treated HIV infection. B cell factors include distinctive EBV latency patterns and host protein expression in HIV-associated LPD, as well as B cell-stimulating factors derived from HIV infection. We review the future directions for expanding therapeutic approaches in targeting the viral and immune components of EBV LPD pathogenesis.